EPIGENETIC EFFECTS OF ENZASTAURIN – A NEW ASPECT IN THE MECHANISM OF ACTION OF AN ANTICANCER DRUG FROM PROTEIN KINASE INHIBITORS - V. P. Maksimova; J. V. Makus; O. G. Usalka; E. S. Lylova; P. E. Bugaeva; E. M. Zhidkova; D. A. Fedorov; O. P. Lizogub; E. A. Lesovaya; G. A. Belitsky; M. G. Yakubovskaya; K. I. Kirsanov (Сибирский онкологический журнал)
The purpose of the study was to analyze the ability of five antitumor drugs from the pharmaceutical group of protein kinase inhibitors (gefitinib, imatinib, pazopanib, ponatinib and enzastaurin) to reactivate the expression of the epigenetically silenced GFP in HeLa TI cells, and to estimate the effect of epigenetically active drugs on: 1) acetylation and methylation of histones H3 and H4; 2) integral DNA methylation; 3) activity of HAT and HDAC1 enzymes; 4) expression levels of the genes encoding epigenetic regulation enzymes (DNMT1, DNMT3A, DNMT3B; SIRT1, HDAC1; SETD1A, SETD1B, SUV420H1, SUV420H2, SUV39H1, SUV39H2). Material and Methods. The epigenetic activity of antitumor drugs was determined using the HeLa TI test system, a population of HeLa cells with the retroviral vector containing the epigenetically silenced GFP. The level of integral DNA methylation was analyzed using MspI/HpaII methyl-sensitive restriction analysis. Histone modifications were analyzed by Western blotting with antibodies to acetylated and methylated histones H3 and H4. The total activity of HAT enzymes was analyzed using Histone Acetyltransferase Activity Assay Kit. Expression of the epigenetic enzyme genes was analyzed using real-time quantitative RT-PCR. Results. It was shown that only the enzyme inhibitor Cβ protein kinase enzastaurin had the ability to reactivate the expression of epigenetically silenced GFP in the HeLa TI cells. We showed that under the action of enzastaurin, the level of integral DNA methylation and expression of DNMT3A and DNMT3B DNA methyltransferase genes decreased. It was also found that enzastaurin reduced the expression levels of histone deacetylases HDAC1 and SIRT1, but did not affect the activity and expression levels of histone acetylases, the level of histone methylation (H3K4me3, H3K9me3, H3K27me3, H4K20me3), and the level of expression of the histone methyltransferases (SUV39H1, SUV39H2, SUV420H1, SUV420H2, SETD1A и SETD1B). Conclusion. The data obtained are important for clarifying the mechanisms of action of 5 protein kinase inhibitors, in particular with respect to enzastaurin, the protein kinase Cβ inhibitor, for which the ability to reactivate epigenetically silent genes due to the effect on DNA methylation and histone acetylation was demonstrated.